An examination of the role of review valence and review source in varying consumption contexts on purchase decision. (January 2020) - Tata, Sai Vijay; Prashar, Sanjeev; Gupta, Sumeet
Abstract: This study examines the influence of Valence and Source of Online Reviews on a customer's attitude and purchase decision in the context of public and private consumption using social influence theory and the concept of negativity bias. The study was conducted using a 2 × 3 × 3 online experiment to examine the influence of review valence (positive vs mixed vs negative), two sources (retailer vs third-party site) in two different consumption contexts (public vs private). The results highlight the role of review valence as well as consumption context on a shopper's decision.